Structural characterization, acute toxicity assessment and protective effects of selenylated apple pectin on dextran sulfate sodium-induced ulcerative colitis. Issue 13 (21st June 2022) - Tao, Wen; An, Xiaoyu; Guo, Ziqi; Yang, Ning; Wu, Muci; Oliveira, Hélder; Zhang, Rui; He, Jingren
Abstract : This study was aimed at investigating the structural characterization, acute toxicity and protective effect of selenylated apple pectin on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in mice. Abstract : This study was aimed at investigating the structural characterization, acute toxicity and protective effect of selenylated apple pectin on dextran sulfate sodium (DSS)-induced ulcerative colitis (UC) in mice. Selenylated apple pectin was characterized by ion chromatography, NMR and SEC-RI-MALLS. The acute toxicity and protective effect of selenylated apple pectin against UC were investigated by gavage administration in mice. The organ state and coefficients, inflammatory cytokine (IL-6, IL-10 and TNF-α) contents in serum, GSH-Px activity and MPO content in colon tissues were also evaluated. The results indicated that selenylated apple pectin was non-toxic and contained 244.28 μgselenium per g. The monosaccharide composition with different molar ratios, different relative molecular weights and a weakened signal peak (CH2 –O group) at 3–4 ppm were observed after selenylation. The selenylated apple pectin showed the protective effect against UC by down-regulating IL-6 and TNF-α contents and up-regulating the IL-10 content in serum, as well as increasing the GSH-Px activity and decreasing the MPO content in colon tissues. Moreover, DSS-induced alterations were effectively recovered by a high-dose sample. These findings provide evidence in support of selenylated apple pectin as a novel dietary selenium supplement for UC protection.